(untitled) (The Research of Medical Science Review, 2024)
There are many obstacles when it comes to MHM in Pakistan, particularly in remote areas like Gilgit-Baltistan. A lack of education, obstacles due to culture and insufficient infrastructure create problems in menstrual health and result in major social stigma. The research combined PDHS 2016-17 data with analyses of peer-reviewed articles from different regions of Pakistan. The study explored what urban and rural women in Gilgit-Baltistan knew, believed and practiced about menstruation.Urban women were found to be twice as likely to know about menstruation as rural women: 64.5% in urban places, but only 25.9% in rural places. Urban women chose commercial pads, whereas rural women mainly depended on washing and reusing cloths since sanitation was poor. The presence of cultural stigma was common and it was stronger in the countryside than in the cities. More than half the women were not trained which made it less likely that they knew how to care for their menstrual health and where to buy safe products. It is important to address MHM in Gilgit-Baltistan with interventions that are culturally aware and specific to the region, so people can learn more, find products and stop feeling stigma around the subject. When MHM becomes a part of health services and collaborative efforts, it gives better support to women in need in such communities. This study covers menstrual hygiene management in Gilgit-Baltistan, differences in menstrual care between urban and rural areas, the stigma of menstruation and how all of this affects Pakistan.